A New Paradigm in Islamic Housing: Non-Bank Islamic Mortgage - Egi Arvian Firmansyah; Ardi Gunardi (Faculty of Shariah and Law, UIN Syarif Hidayatullah Jakarta, 2018)
An increasing demand for a sharia-compliant housing has resulted in a new initiative where the mortgage can presently be directly handled by the developer without involving the bank. This is called non-bank Islamic mortgage. This paper is aimed at portraying the consumer’s profile of non-bank Islamic mortgage and the issues of this practice. We disseminated questionnaires to the respondents in several cities in West Java who bought the house-using non-bank Islamic mortgage scheme. Subsequently, we synthesized the answers regarding their profiles and issues of the scheme for the betterment in the future. One of the issues of this scheme is the higher fraud because there is no rigorous credit scoring as conducted by the bank. The research of non-bank Islamic mortgage is still scant so this paper is expected to shed the light by contributing to the literature of Islamic home financing.DOI: 10.15408/aiq.v10i2.7274